Enhancing rapid nitrogen freezer performance for Litchi fruit: a Taguchi-based approach to reduce cracking, time, and nitrogen consumption - Mohamed Anwer Abdeen; Zeyong Zheng; Xiaojin Cheng; Baiqing Yu; Chongyang Han; Yong Cao; Wenquan Huang; Ali Salem; Alaa Awny; Weibin Wu (Scientific Reports)
Abstract This study employed the Taguchi technique to investigate the influence of various liquid nitrogen quick-freezing parameters on litchi fruit cracking, nitrogen consumption, and freezing time. The experiments included testing different freezing temperatures (− 40, − 50, − 60, and − 70 °C), two types of nitrogen spraying nozzles (Hollow-cone and Full-cone), and two fan speeds (800 and 1200 rpm). Before freezing, the litchis were soaked in a solution and precooled as a pre-treatment to mitigate peel cracking and preserve quality. The results revealed that the crack ratio, freezing time, and nitrogen consumption decreased as temperature and fan speed increased. Among the nozzle types, Full-cone nozzles exhibited superior performance, achieving reductions of more than 15% in crack ratio, over 8% in freezing time, and more than 4% in nitrogen consumption compared to Hollow-cone nozzles. The predicted values derived from the Taguchi method showed strong alignment with the experimental data, validating the robustness of the optimization approach. This study contributes novel insights to the field of food freezing technology by introducing an innovative method for minimizing fruit cracking during freezing without the need for packaging. The findings also highlight the potential for reducing freezing time, operational costs, and nitrogen usage, offering practical implications for the food processing industry.